EFFECT OF OCCUPATIONAL HEALTH AND SAFETY ON EMPLOYEE PERFORMANCE IN FISHING COMPANIES - Aprianti, Neni Nur Aini; Almansur, Fauzan (Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2022)
This study aims to analyze the effect of occupational safety and health on employee performance. The study was conducted in Istanbul Fursesaine Jembrana Bali with a sample of 71 respondents. It uses PLS and SPSS analysis methods. Based on the research results, the occupational health variable significantly negatively affects employee performance. This is because before the prospective employee is accepted to work at Istanbul Fursesaine, the company ensures the health of its employees or health selection that the condition is healthy. After all, in connection with the work to be carried out by the employee, it is a job that requires individuals to have a muscular physique. Then the work safety variable has a significant positive effect on employee performance. The importance of safety for employees is the obligation of all companies to use safety equipment by predetermined standards. Furthermore, occupational health and safety variables simultaneously affect employee performance. This test can test a simultaneous test with SPSS, namely the F test so that occupational health and safety affect employee performance. So can conclude that occupational safety and health affect employee performance.